Analysis of Student Learning Experiences: Differences in Abilities and Perceptions towards Research Methodology - Wiwit Artika; Dewi Andayani; Yaumil Istiqlal M. Nur; Hendra Yulisman (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2019)
The purpose of this study is to compare several skill aspects of graduate students in research methodology-based subjects and to find out their perceptions about the definition of research and challenges in understanding the course. This study is a survey research using a mix methods case study approach. The sample was chosen purposively consisted of 10 postgraduate students at the University of Arkansas (UARK) and several universities in the United Kingdom (UK). The results of t-test analysis showed that there were no significant differences in reading skills, writing skills, and finding resources between Indonesian graduate students of the UARK and UK which were calculated for t (8) = -2.08, p = .07, t (8) = - 1.98, p = .08, and t (8) = -.92, p = .39 respectively. Most postgraduate students in Indonesia define research as a systematic study. Language and technical terms are the biggest challenges that would be faced to understand research-based course content.